2014
DOI: 10.1055/s-0034-1377558
|View full text |Cite
|
Sign up to set email alerts
|

Core biopsy needle versus standard aspiration needle for endoscopic ultrasound-guided sampling of solid pancreatic masses: a randomized parallel-group study

Abstract: The overall accuracy of FNB and FNA in patients with solid pancreatic masses was comparable; however, fewer passes were required to establish the diagnosis of malignancy using FNB.This study was registered on the UMIN Clinical Trial Registry (UMIN000014057).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
145
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 20 publications
13
145
2
Order By: Relevance
“…However, this study used suction during procurement of FNB, which may have increased the bloodiness and contamination of specimens. Two recently published prospective, randomized trials have also shown no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreas mass lesions [44,45]. Consistent with the previously published literature, results from this randomized controlled trial also showed no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreatic masses (FNB: 91.7 %, FNA: 78.4 %, P = 0.19).…”
Section: Discussionsupporting
confidence: 89%
“…However, this study used suction during procurement of FNB, which may have increased the bloodiness and contamination of specimens. Two recently published prospective, randomized trials have also shown no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreas mass lesions [44,45]. Consistent with the previously published literature, results from this randomized controlled trial also showed no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreatic masses (FNB: 91.7 %, FNA: 78.4 %, P = 0.19).…”
Section: Discussionsupporting
confidence: 89%
“…The authors used both core biopsy and cytoblock for the diagnosis, so we do not know how much a contribution the core biopsy made by itself. A second study, focused on the 22G FNA standard needle, with a median of two passes, showed that the accuracy for histology was 82% and the sensitivity was only 81%, in the conditions of splitting samples for two cytology examinations and for histology, a fact which could diminish the diagnostic yield [20]. A similar accuracy (82.5%) was obtained in a third study with two passes of FNA.…”
Section: Discussionmentioning
confidence: 70%
“…This study also reported on high rates of IHC being performed on both the FNA (78%) and FNAB (83%) acquired tissue. 35 Although intuitively, one would expect higher tissue-grade material and diagnostic yield with these newer ProCore needles, the current randomized data from pancreatic masses show equivalency with regular FNA with respect to both diagnostic yield and overall histological tissue grade. However, there may be a trend toward fewer passes to establish the diagnosis using FNAB ProCore needles and hence shorter procedures times.…”
Section: Pancreas Eus-fnab With High-definition Core Biopsy Needlementioning
confidence: 92%
“…Interestingly, both pathologists found the overall sample quality significantly better for the standard FNA needle (expert 1, P = 0.009; expert 2, P = 0.002). 34 Finally, Lee et al 35 prospectively randomized 116 consecutive patients with solid pancreatic masses to EUS-FNAB using either a 22-gauge (transgastrically) or 25-gauge (transduodenally) FNAB ProCore biopsy needle or EUS-FNA using a standard aspiration 22-gauge (transgastrically) or 25-gauge (transduodenally) needle. A portion of the material obtained was smeared onto 3 to 5 glass slides for on-site analysis and Papanicolaou stain cytology, with the residual tissue placed into 2 or 3 wells of a tissue tray with formalin for histological analysis.…”
Section: Pancreas Eus-fnab With High-definition Core Biopsy Needlementioning
confidence: 99%